2021
DOI: 10.1002/ceat.202100124
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Main Components in Paper‐Plastic‐Aluminum Complex Packaging Wastes during the Hydrothermal Liquefaction Process

Abstract: Hydrothermal liquefaction was applied to treat paper-plastic-aluminum (Al-PE-Pa) complex packaging waste for bio-oil production. The interactive effects between the main components of paper fiber, low-density polyethylene (LDPE), and aluminum foil in such complex material were studied. The co-liquefaction of paper fiber and LDPE had a significant synergistic effect. The addition of hydrogen-rich LDPE effectively promoted the removal of oxygen-containing groups. Aluminum foil had only a slight impact on the liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…RS decomposed before LLDPE, and the generated products from RS played the role of a reactant in promoting degradation of LLDPE, resulting in a high oil yield and the corresponding low solid yield . In detail, the hydrogen and alkyl radical abstraction by RS-derived oxygenates and reactive free radicals could facilitate the scission of polymer chains and their derivatives; (2) the presence of alkali and alkaline earth metals in the biomass (Table ) could be activated to act as a pro-oxidant for LLDPE during coprocessing, generating radicals on the polymer chain, which could then undergo oxidation or chain scission. ,, This chemistry promoted degradation of LLDPE, thus increasing the oil yield; (3) the positive effect of ash and fixed carbon on solid product formation was weakened because of their lower content in feedstock; (4) the interplay between RS and LLDPE restricted the secondary cracking of oils, e.g., cyclization, condensation, and polymerization, resulting in a low solid yield and a high oil yield; and (5) part of methanol (about 0.13 wt %) as a reactant in the degradation of the mixture led to a positive effect on the formation of oil.…”
Section: Resultsmentioning
confidence: 99%
“…RS decomposed before LLDPE, and the generated products from RS played the role of a reactant in promoting degradation of LLDPE, resulting in a high oil yield and the corresponding low solid yield . In detail, the hydrogen and alkyl radical abstraction by RS-derived oxygenates and reactive free radicals could facilitate the scission of polymer chains and their derivatives; (2) the presence of alkali and alkaline earth metals in the biomass (Table ) could be activated to act as a pro-oxidant for LLDPE during coprocessing, generating radicals on the polymer chain, which could then undergo oxidation or chain scission. ,, This chemistry promoted degradation of LLDPE, thus increasing the oil yield; (3) the positive effect of ash and fixed carbon on solid product formation was weakened because of their lower content in feedstock; (4) the interplay between RS and LLDPE restricted the secondary cracking of oils, e.g., cyclization, condensation, and polymerization, resulting in a low solid yield and a high oil yield; and (5) part of methanol (about 0.13 wt %) as a reactant in the degradation of the mixture led to a positive effect on the formation of oil.…”
Section: Resultsmentioning
confidence: 99%
“…Except for the potential hydrogen source and promoter, water could serve as a reactant to produce hydrogen and alcohol, aldehyde, acid and other oxygencontaining derivatives in the hydrothermal liquefaction of polyethylene to oil. 43,44 Similarly, Guo and Luo et al 45,46 also found H 2 O in the hydrothermal conditions could directly participate in hydrodenitrogenation reactions of nitrogen-containing heterocyclic substances, in which the oxygen-containing compounds were generated from the interaction with water.…”
Section: The Role Of Water For Co Hydrogenation In Hydrothermal Condi...mentioning
confidence: 97%
“…Moreover, the existence of molecular H 2 O could also act as a proton acceptor to form the H 3 O + like cation conformation during the transition state of methanol, significantly decreasing the activation energy of methanol oxidation from 378 kJ/mol to 220 kJ/mol. Except for the potential hydrogen source and promoter, water could serve as a reactant to produce hydrogen and alcohol, aldehyde, acid and other oxygen‐containing derivatives in the hydrothermal liquefaction of polyethylene to oil 43,44 . Similarly, Guo and Luo et al 45,46 also found H 2 O in the hydrothermal conditions could directly participate in hydrodenitrogenation reactions of nitrogen‐containing heterocyclic substances, in which the oxygen‐containing compounds were generated from the interaction with water.…”
Section: The Role Of Water For Co2 Hydrogenation In Hydrothermal Cond...mentioning
confidence: 99%
“…One of the proposed methods for paper or paperboard-containing multilayer materials, includes package disintegration, filtering the cellulose pulp suspension, aluminum and polyethylene delamination with formic acid, and the extraction of microcrystalline cellulose using sulfuric acid [ 96 ]. Other techniques include pyrolysis, low-temperature torrefaction, hydrothermal liquefaction (HTL), and hydrothermal carbonization (HTC) [ 97 , 98 , 99 , 100 ]. For aluminum recovery, a number of methods have been proposed as well.…”
Section: Introductionmentioning
confidence: 99%